Development of Flipbook Learning Media Based on Problem Based Learning (PBL) on Acid Base Material to Increase Students Digital Literacy - Ramadhan, Sarah Afillah; Haryanto, Haryanto; Hasibuan, Muhammad Haris Effendi (ALACRITY : Journal of Education, 2025)
This research is part of research into the development of flipbook learning media based on problem-based learning on acid-base material to increase students' digital literacy. The aim of this research is to determine the process of developing learning media in the form of flipbooks based on Problem Based Learning (PBL) in learning acid-base material. Students' digital literacy is the main focus in this development. This research uses a Research and Development (R&D) approach with a 4D model consisting of definition, design, development and deployment. The trial was carried out at SMA Negeri 13 Jambi City. The results of this research obtained an average score from media experts of 4.75 "very appropriate" and material experts of 4.64 "very appropriate". Furthermore, based on the teacher's responses and assessments, an average score of 4.75 "very adequate" was obtained. Then it also received a very good response from students on a scale of 5 with an average score of 88.6% "very good". And for students' digital literacy skills on a scale of 5 it reached 84.4% "very good".